2004
DOI: 10.1111/j.1651-2227.2004.tb02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of anti‐secretory factor in human milk may prevent mastitis

Abstract: Aim: The aim of the study was to try to induce anti‐secretory factor (AF) in human milk and possibly prevent mastitis. Methods: Forty mothers who had normal deliveries and healthy full‐term infants were randomly divided into two groups, 3–7 days postpartum. The experimental group received a food inducing AF. The control group received the same type of food, without AF‐inducing properties. Milk was tested for AF after the mothers had eaten the cereals for 4–5 wk. AF was determined by intravenous injection of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 77 publications
(107 reference statements)
0
17
0
1
Order By: Relevance
“…It appears in human milk and has been shown in a placebo-controlled study to prevent clinical mastitis (Svensson et al 2004). In a double-blind placebo-controlled study of acute or prolonged diarrhoea in 240 Pakistani children (Zaman et al 2007) it was found to be protective.…”
Section: Anti-secretory Factormentioning
confidence: 99%
See 1 more Smart Citation
“…It appears in human milk and has been shown in a placebo-controlled study to prevent clinical mastitis (Svensson et al 2004). In a double-blind placebo-controlled study of acute or prolonged diarrhoea in 240 Pakistani children (Zaman et al 2007) it was found to be protective.…”
Section: Anti-secretory Factormentioning
confidence: 99%
“…The human peptide anti-secretory factor, which can be induced in human milk (Svensson et al 2004), has recently been shown to give protection against acute diarrhoea as well as prolonged diarrhoea (Zaman et al 2007). A Mexican study ) has shown that breast-feeding is associated with a 5-fold lower risk of diarrhoea caused by G. lamblia compared with no breast-feeding, and a 1 .…”
Section: Breast-feeding and Diarrhoeamentioning
confidence: 99%
“…It is present in most human tissues, and it is especially rich in fluid‐transporting epithelia, certain endocrine cells, neurons and immune cells. Intestinal exposure to bacterial toxins or intake of specific dietary compounds have proved to enhance the anti‐secretory and anti‐inflammatory activity of endogenous AF and induction of AF in humans have proved to prevent mastitis . Whether the mother's AF levels may influence oral colonisation of the infant is unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Dosing and mode of administration of B 221 are still yet to be understood, but according to the authors, a higher dosage might be useful in the management of acute diarrhoea in children, especially in developing countries, avoiding the appearance of prolonged diarrhoea, with its threatening consequences (12) . Svensson et al (97) found that AF can be induced in maternal milk by hydrothermally processed cereal intake. Furthermore, the AF-inducing diet prevented mastitis, a painful infection and inflammation of the breast tissue, probably due to the anti-inflammatory properties of AF.…”
Section: Antisecretory Factor and Endocrine Diarrhoeamentioning
confidence: 99%